2021
DOI: 10.3389/fpsyg.2021.573123
|View full text |Cite|
|
Sign up to set email alerts
|

Proximate and Ultimate Perspectives on Romantic Love

Abstract: Romantic love is a phenomenon of immense interest to the general public as well as to scholars in several disciplines. It is known to be present in almost all human societies and has been studied from a number of perspectives. In this integrative review, we bring together what is known about romantic love using Tinbergen’s “four questions” framework originating from evolutionary biology. Under the first question, related to mechanisms, we show that it is caused by social, psychological mate choice, genetic, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(133 citation statements)
references
References 266 publications
(520 reference statements)
5
128
0
Order By: Relevance
“…The neuropeptides oxytocin and vasopressin and the neurotransmitter dopamine facilitate pair-bonding, while polymorphisms in oxytocin, vasopressin, and dopamine genes, and their receptor-rich brain regions, are involved in basic motivational processes, sexual satisfaction, and pair-bonding across species (Acevedo, Poulin, Collins, & Brown, 2020;Diekhof, Richter, Brodmann, & Gruber, 2021). These kinds of findings provide evidence that pair-bonding and romantic love maintenance in humans are parts of a broad mammalian strategy for reproduction and long-term attachment which is influenced by basic reward circuitry and genetic factors that create individual differences in sexual behaviors, sexual preferences, and pair-bonding (Acevedo et al, 2020;Bode & Kushnick, 2021;Luoto et al, 2019a). For more detailed discussions of these topics, readers may wish to refer to Acevedo et al (2020) who used a mixed methods approach-both neuroimaging and gene samplingto study how genetic polymorphisms and brain activation are related to romantic love in newlywed couples (see also Bode & Kushnick, 2021, for a broader review).…”
Section: Other Behavioral and Molecular Genetics Studies In Evolutionary Sex Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…The neuropeptides oxytocin and vasopressin and the neurotransmitter dopamine facilitate pair-bonding, while polymorphisms in oxytocin, vasopressin, and dopamine genes, and their receptor-rich brain regions, are involved in basic motivational processes, sexual satisfaction, and pair-bonding across species (Acevedo, Poulin, Collins, & Brown, 2020;Diekhof, Richter, Brodmann, & Gruber, 2021). These kinds of findings provide evidence that pair-bonding and romantic love maintenance in humans are parts of a broad mammalian strategy for reproduction and long-term attachment which is influenced by basic reward circuitry and genetic factors that create individual differences in sexual behaviors, sexual preferences, and pair-bonding (Acevedo et al, 2020;Bode & Kushnick, 2021;Luoto et al, 2019a). For more detailed discussions of these topics, readers may wish to refer to Acevedo et al (2020) who used a mixed methods approach-both neuroimaging and gene samplingto study how genetic polymorphisms and brain activation are related to romantic love in newlywed couples (see also Bode & Kushnick, 2021, for a broader review).…”
Section: Other Behavioral and Molecular Genetics Studies In Evolutionary Sex Researchmentioning
confidence: 91%
“…These kinds of findings provide evidence that pair-bonding and romantic love maintenance in humans are parts of a broad mammalian strategy for reproduction and long-term attachment which is influenced by basic reward circuitry and genetic factors that create individual differences in sexual behaviors, sexual preferences, and pair-bonding (Acevedo et al, 2020;Bode & Kushnick, 2021;Luoto et al, 2019a). For more detailed discussions of these topics, readers may wish to refer to Acevedo et al (2020) who used a mixed methods approach-both neuroimaging and gene samplingto study how genetic polymorphisms and brain activation are related to romantic love in newlywed couples (see also Bode & Kushnick, 2021, for a broader review). Another study by Diekhof and colleagues (2021) genotyped participants for genetic polymorphisms in the dopamine system and created a multilocus genetic composite (MGC) score which reflected the additive effect of different alleles conferring relative increased dopamine transmissionwhich in turn influences reward processes and behaviors across species (see also Kringelbach & Berridge, 2010;Luoto et al, 2019b;Struik, Sanna, & Fattore, 2018).…”
Section: Other Behavioral and Molecular Genetics Studies In Evolutionary Sex Researchmentioning
confidence: 95%
“…Given that there is some evidence that depression symptoms scores are associated with romantic love (including among adolescents), it raises the question of why this is the case. Similar or related biological mechanisms may be one explanation (see Bode & Kushnick, 2021). Both depression and romantic love are associated with changes in functional connectivity in networks involving the amygdala, medial prefrontal cortex, and nucleus accumbens (Dean & Keshavan, 2017;Song et al, 2015).…”
Section: Neural and Endocrinological Activitymentioning
confidence: 99%
“…It is common at the beginning of a romantic relationship but can occur in the absence of a romantic relationship. The mechanisms that cause romantic love, its development across the lifespan, its functions, and its evolutionary history have been described in detail elsewhere (Bode & Kushnick, 2021). That review suggested that romantic love has neurobiological and endocrinological similarities with depression.…”
Section: Romantic Lovementioning
confidence: 99%
See 1 more Smart Citation